Recognition and Empirical Research on Key Influencing Factors of Low Carbon Development for Logistics Company - Xiang-Yun Duan; Hsiu-Jung Chou; Shuenn-Ren Cheng (Discrete Dynamics in Nature and Society)
The questionnaire paper used was work out by modifying the existing mature research scale and interviewing the experts and enterprises. The purpose of this study is to explore the key influencing factors of low carbon development for logistics companies by using the data from the questionnaire, which might contribute to further investigation of low carbon development pathway. Through correlation and stepwise regression analysis, differences between influencing factors and impact-degree were found since specific environmental behaviors of low carbon logistics might vary significantly. The driving factor of low carbon input comes from external points such as government and public external pressure, so the low carbon input is driven by an outside force. Yet, low carbon operation is significantly affected by internal factors such as low carbon behavior capacity, which is driven by an inside force.